Kawasaki Disease and Pyelonephritis: A Case Report: Kawasaki disease, and pyelonephritis - Mojtahedi, Sayed Yousef; Noparast, Zahra; Shahnazizadeh , Amir; Talebi , Ali; Kajiyazdi, Mohammad (Journal of Pediatric Nephrology, 2022)
Kawasaki disease is a form of vasculitis, mainly in small and medium-sized arteries of unknown origin, and often occurs in childhood. It is the leading form of heart disease acquired in childhood in developed countries. Pyelonephritis is not usually associated with Kawasaki, but hereby we represent a case of Kawasaki disease associated with pyelonephritis; however, we can’t say whether pyelonephritis had a role in stating Kawasaki and it could be a proper and valuable topic for research.